2017
DOI: 10.1016/j.bbmt.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Survival Advantage and Comparable Toxicity in Reduced-Toxicity Treosulfan-Based versus Reduced-Intensity Busulfan-Based Conditioning Regimen in Myelodysplastic Syndrome and Acute Myeloid Leukemia Patients after Allogeneic Hematopoietic Cell Transplantation

Abstract: Treosulfan has been incorporated in conditioning regimens for sustained remission without substantial toxicity and treatment-related mortality (TRM). We aimed to analyze the safety and efficacy of a fludarabine 150 mg/m and treosulfan 42 g/m (FluTreo) conditioning regimen in medically infirm patients. Outcomes were compared with those of a similar historical group treated with fludarabine 150 mg/m to 180 mg/m, busulfan 6.4 mg/kg, and antithymocyte globulin (ATG) 5 mg/kg to 7.5 mg/kg (FluBuATG). Thirty-one cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
5
19
0
Order By: Relevance
“…Although HCT using nonmyeloablative conditioning was effective at correcting the underlying hematologic, immunologic and clinical manifestations of GATA2 deficiency, the authors stated that they are currently investigating a more intensive conditioning regimen consisting of busulfan and fludarabine with the goal of decreasing the risk of rejection and relapse. Our results as well as other published studies using treosulfan-based conditioning for patients with MDS/AML support that treosulfan-based conditioning may be another viable option for patients with GATA2 deficiency [4345]. …”
Section: Discussionsupporting
confidence: 87%
“…Although HCT using nonmyeloablative conditioning was effective at correcting the underlying hematologic, immunologic and clinical manifestations of GATA2 deficiency, the authors stated that they are currently investigating a more intensive conditioning regimen consisting of busulfan and fludarabine with the goal of decreasing the risk of rejection and relapse. Our results as well as other published studies using treosulfan-based conditioning for patients with MDS/AML support that treosulfan-based conditioning may be another viable option for patients with GATA2 deficiency [4345]. …”
Section: Discussionsupporting
confidence: 87%
“…Ruutu et al [33] showed a 17% incidence of NRM and a 71% OS at 2 years in MDS patients conditioned with treosulfan. Casper et al [14] observed an NRM of 11% and an OS of 61% in a mixed cohort of patients, and Sakellari et al [34] showed, in a retrospective analysis, a survival advantage for patients with AML or MDS conditioned with a fludarabine (150 to 180 mg/m 2 )/ treosulfan (42 g/m 2 ) regimen in comparison with patients conditioned with fludarabine (150 to 180 mg/m 2 )/busulfan (6.4 mg/kg i.v.) (OS 76% versus 57%; PFS 70% versus 38%, respectively [P < .001]) without an increase in toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…A Treo‐based conditioning regimen for hematological malignant and nonmalignant diseases has proven to be beneficial in patients undergoing allogeneic HSCT, especially as an attractive alternative to a busulfan‐based regimen. Although the dose‐limiting toxicity and maximum tolerated dose of Treo have been documented, the PK and PD of Treo have not been extensively reported in the HSCT setting.…”
Section: Discussionmentioning
confidence: 99%